2013
DOI: 10.1192/apt.bp.110.008243
|View full text |Cite
|
Sign up to set email alerts
|

The role of mentalising in the management of violence

Abstract: SummaryViolence between people is a complex social phenomenon involving both social and individual psychological variables. Prevention of violence includes attention to risk factors for violence; but also the provision of interventions for those who have been violent to others. This article explores the evidence that failures of the mentalising process are a risk factor for acts of violence, especially in mental health service users; and describes the implementation of potential therapeutic programmes that see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…Planning deficiencies increase the probability of violence by negatively affecting a person's ability to assess the possible consequences of his or her actions (Meijers et al, 2017). Impairments in ToM may lead to violence through misinterpretation of social cues (Adshead et al, 2013), underregulation of negative emotions (Fonagy and Luyten, 2009), blurring of self-other boundaries (Adshead et al, 2013) or lack of empathy (Hooker et al, 2008). There was no significant difference between violent and nonviolent patients in affective ToM, which is arguably more important for the last three than cognitive ToM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Planning deficiencies increase the probability of violence by negatively affecting a person's ability to assess the possible consequences of his or her actions (Meijers et al, 2017). Impairments in ToM may lead to violence through misinterpretation of social cues (Adshead et al, 2013), underregulation of negative emotions (Fonagy and Luyten, 2009), blurring of self-other boundaries (Adshead et al, 2013) or lack of empathy (Hooker et al, 2008). There was no significant difference between violent and nonviolent patients in affective ToM, which is arguably more important for the last three than cognitive ToM.…”
Section: Discussionmentioning
confidence: 99%
“…Since EFs and ToM are essential for social adaptation, impairments in these cognitive functions are thought to underlie violent behavior. However, causal mechanisms likely differ by EF (Raine, 2008) and ToM type (Adshead et al, 2013). General population studies have repeatedly found that people who display violent behavior perform worse on neuropsychological tests of EFs (Ogilvie et al, 2011) and ToM (Hoaken et al, 2007; Nyline et al, 2018) than those who do not.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, expectations that certain populations (e.g. those with personality disorder or prone to violence) will lack reflective function have not been consistently supported (Tolfree, 2012;Adshead, 2013). The conundrum of reflective function and whether certain groups lack it is somewhat redolent of the 'cognitive deficits' debate in the probation world.…”
Section: The Reflective Function and Mentalizationmentioning
confidence: 99%
“…Violent offenders may be divided into a highaffect, impulsive and hyperaroused group, and a low-affect, unemotional and psychopathic group (Meloy 2006;Adshead 2013). The first group are more likely to become violent in response to perceived threats to their sense of self.…”
Section: Violence and Mentalisationmentioning
confidence: 99%